Dopaminergic Projections From the Ventral Tegmental Area to the Nucleus Accumbens Modulate Sevoflurane Anesthesia in Mice - Gui, Huan; Liu, Chengxi; He, Haifeng; Zhang, Jie; Chen, Hong; Zhang, Yi (Frontiers in cellular neuroscience, 2021)
The role of the dopaminergic pathway in general anesthesia and its potential mechanisms are still unknown. In this study, we usedc-Fos staining combined with calcium fiber photometry recording to explore the activity of ventral tegmental area (VTA) dopaminergic neurons(VTA-DA) and nucleus accumbens (NAc) neurons during sevoflurane anesthesia. A genetically encoded dopamine (DA) sensor was used to investigate thefunction of the NAc in sevoflurane anesthesia. Chemogenetics and optogenetics were used to explore the role of the VTA-DA in sevofluraneanesthesia. Electroencephalogram (EEG) spectra, time of loss of righting reflex (LORR) and recovery of righting reflex (RORR) were recorded asassessment indicators. We found that VTA-DA and NAc neurons were inhibited during the induction period and were activated during the recoveryperiod of sevoflurane anesthesia. The fluorescence signals of dopamine decreased in the induction of and increased in the emergence from sevoflurane anesthesia.Activation of VTA-DA and the VTA DA -NAc pathway delayed the induction and facilitated the emergence accompanying with thereduction of delta band and the augmentation of the gamma band. These data demonstrate that VTA-DA neurons play a critical role in modulating sevofluraneanesthesia via the VTA DA -NAc pathway.